Characterization of G -Semigroup by Intuitionistic N-Fuzzy Set (INFS) and its level set - Muhammad Akram, Muhammad Akram; Kavikumar, Jacob; Iqbal, Zaffar (Natural Sciences Publishing Cor., 2017)
Some characterizations of G -Semigroup by intuitionistic N-fuzzy sets have been given here. The concept of intuitionistic N-fuzzy set (INFS) and its level set has been applied to G -semigroup. The notions of intuitionistic N-fuzzy G -subsemigroup and intuitionistic N-fuzzy G - ideals (left, right, lateral, quasi, and bi) have been introduced and characterized by intuitionistic N-fuzzy sets.